2013 ASEE Annual Conference &Amp; Exposition Proceedings
DOI: 10.18260/1-2--22592
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Inclusive Excellence Programs on the Development of Engineering Identity among First-Year Underrepresented Students

Abstract: is the engineering assessment specialist at the Integrated Teaching and Learning Program and Laboratory. He holds a BA in psychology from Louisiana State University, and an MS degree in industrial/organizational psychology and PhD degree in counseling psychology, both from the University of Tennessee. Prior to joining the University of Colorado at Boulder, he gained extensive experience in assessment and teamwork in an engineering education context through the development and evaluation of a team facilitation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 11 publications
1
9
0
Order By: Relevance
“…This design describes assessment plans that involved collecting data before and after an intervention, typically the same types of data, to demonstrate growth and development. For example, D. Knight et al (2013) administered pre-and post-surveys to measure identity development in program participants. One survey was administered before and after two summer bridge programs.…”
Section: Pretest-posttestmentioning
confidence: 99%
See 1 more Smart Citation
“…This design describes assessment plans that involved collecting data before and after an intervention, typically the same types of data, to demonstrate growth and development. For example, D. Knight et al (2013) administered pre-and post-surveys to measure identity development in program participants. One survey was administered before and after two summer bridge programs.…”
Section: Pretest-posttestmentioning
confidence: 99%
“…For example, Donnelly (2007) constructed survey items specifically related to program components, such as monthly meetings or the computer and teaching training they received to measure how agreeable the students were to the fact that these components were beneficial to their development. For the articles using established questionnaires, aspects of validity or reliability were reported in the text or pointed to previously reported literature (Di Salvo et al, 2013;Dunn & Veltman, 1989;D. Knight et al, 2013;B.…”
Section: Nonexperimental-summativementioning
confidence: 99%
“…Chachra et al (2008) identified four dimensions of engineering identity: (1) centrality refers to the extent to which a student views themselves as an engineer (e.g., "Being an engineering student is an important reflection of who I am"), (2) private regard refers to the extent to which a student feels positively or negatively about engineering and engineers (e.g., "I feel good about engineers"), (3) public regard refers to a student's perception of other's feeling about engineering and engineer (e.g., "Overall, engineers are considered good by others"), and (4) group identification refers to the value a student places on being an engineer and the emotional-affective dimensions of belonging to this group (e.g., "I am glad to belong to a group of engineering students"). Although this measure has been utilized in several studies (e.g., Chachra et al, 2008;Knight et al, 2013), its psychometric properties, such as reliability and factor structure, were not appraised. Carlone and Johnson (2007) proposed an important theoretical framework centered around the multidimensional nature of science identity.…”
Section: Measuring Engineering Identitymentioning
confidence: 99%
“…Changing U.S. demographics have outpaced the representation of diverse populations in the engineering and STEM workforce. Although engineering education programs have attempted to increase the structural diversity of women students and those of color to rectify this concern, representation has not significantly changed in recent years (Cross & Peretti, 2012;Diekman, Brown, Johnston, & Clark, 2010;Hug, Jurow, & Chi, 2011;Knight et al, 2013).…”
Section: Marginalized Experiences In Engineering Educationmentioning
confidence: 99%